Intencionalidades do uso da robótica pedagógica na educação infantil em artigos científicos à luz da teoria histórico-cultural - Teles, Maria Estely Rodrigues (Universidade Federal de São Carlos, 2022)
A lot of countries use Pedagogical Robotics in Children Education. Teachers’ pedagogical practices require an intentional mediation according to children's needs. In this sense, this research aims to know the intentionalities of the use of Pedagogical Robotics in Early Childhood Education, present in articles indexed in SciELO, Eric, and Scopus, as well as to analyze convergences and divergences between the intentionalities identified, in the light of the Cultural-Historical Theory. We carried out a bibliographical research based on dialectical materialism. The data was analyzed from the perspective of the concepts of Mediation and Higher Psychic Functions. The articles chosen indicated a variety of themes, so that we identified ten intentionalities for the use of robotics in Children's Education. These intentions revolve around three main axes: learning and child development; activity and interaction; teaching and the Early Childhood Education curriculum. We conclude that there is a need for curricular guidelines and governmental incentives in teacher training aimed at an intentional praxis that mediates robotics for the formation of a critical and transforming individual. There is an urgent need to review the intentions of the use of technologies in school education with a focus on child development, without supporting a mercantilist path and the reproduction of capitalist values.
Intentionalities of the use of pedagogical robotics in early childhood education in scientific articles in the light of the cultural-historical theory
Keywords: Robótica pedagógica; Educação infantil; Teoria histórico-cultural; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM